2009
DOI: 10.1007/s12640-009-9083-4
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins: Are They Beneficial in Treating Ethanol Neurotoxicity?

Abstract: Heavy alcohol exposure produces profound damage to the developing central nervous system (CNS) as well as the adult brain. Children with fetal alcohol spectrum disorders (FASD) have a variety of cognitive, behavioral, and neurological impairments. FASD currently represents the leading cause of mental retardation. Excessive alcohol consumption is associated with Wernicke–Korsakoff syndrome (WKS) and neurodegeneration in the adult brain. Although the cellular/molecular mechanism underlying ethanol’s neurotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 132 publications
0
31
0
1
Order By: Relevance
“…23,24 Ethanol causes oxidative stress in neurons in vitro and in vivo. 25 We have previously demonstrated that ethanol induces ROS generation in SH-SY5Y cells. 26 Antioxidants block ethanol-induced LC3 lipidation, suggesting that autophagy is activated in response to ethanol-induced oxidative stress.…”
Section: Discussionmentioning
confidence: 96%
“…23,24 Ethanol causes oxidative stress in neurons in vitro and in vivo. 25 We have previously demonstrated that ethanol induces ROS generation in SH-SY5Y cells. 26 Antioxidants block ethanol-induced LC3 lipidation, suggesting that autophagy is activated in response to ethanol-induced oxidative stress.…”
Section: Discussionmentioning
confidence: 96%
“…31 Ethanol metabolism also causes lipid peroxidation, oxidative stress and ER dysfunction in liver, brain and other organs. 32 We have reported that chronic ethanol feeding to rodents mobilizes adaptive ER stress responses in exocrine pancreas involving the IRE1/XBP1 UPR branch. 6,33 In the absence of this adaptive response there is impaired early onset of protective IRE1/XBP1s signaling, and upregulation of the PERK/CHOP pathway that converge into ER dysfunction and acinar cell pathology that mimics several features of human alcoholic pancreatitis.…”
Section: Discussionmentioning
confidence: 97%
“…58 In neurons, ethanol-induced ROS mainly come from damaged mitochondria and the activation of NOX (NADPH oxidase). [38][39][40]59 NOX-derived production of ROS activates autophagy. 57 Antioxidants partially block ethanol-induced autophagic flux and mitophagy, suggesting that ROS is involved in ethanol activation of autophagy.…”
Section: Oxidative Stressmentioning
confidence: 99%